Analisis Jaringan Komunikasi Warganet Pada Debat Publik Capres-Cawapres Pemilu 2024 Di Media Sosial - Juditha, Christiany; Darmawan, Josep J (Jurnal Pekommas, 2024)
The public debate of the Presidential Candidates in the 2024 Election is a campaign agenda from the KPU to get public attention. The debate is broadcast live streaming on TVRI's YouTube channel so that it can give voters an idea to determine their preferences and allow the public to participate directly. Participation in the comments section can be studied as a communication network and is also fundamental in developing democracy.. The purpose of this study is to get an overview of the communication network of netizens in the public debate of the 2024 Election Candidates on social media. This research method is Social Media Analysis. The results show that the complete communication network formed had a relatively small diameter, low inter-participant bonding and centralization, the absence of two-way communication, the presence of isolated individuals, and participant accounts that could not be ascertained to be genuine/fake. However, the modularity is quite high, which indicates that clusters are separated by different communities. The communication network in the presidential debate is generally characterized by the community supporting candidate pair number 3 which occupies cluster 1, while candidate pair number 1 supporters are the prominent community in the Vice President debate. Both of these communication networks contain a lot of derogatory comments, bullying, and also hate speech against opponents. Communication networks found in such characteristics tend to be fragile and distortive to be understood as forms of political education, public space, or constructive democratic development.